2019
DOI: 10.1021/acsami.9b00599
|View full text |Cite
|
Sign up to set email alerts
|

Morphology Tuning of ZnO/P3HT/P3HT-b-PEO Hybrid Films Deposited via Spray or Spin Coating

Abstract: Hybrid films of zinc oxide (ZnO) and poly(3-hexylthiophen-2,5-diyl) (P3HT) show promising characteristics for application in hybrid bulk-heterojunction solar cells (HBSCs). However, the incompatibility of ZnO and P3HT may lead to a reduced interface area, thus reducing the probability of exciton separation and consequently lowering solar cell efficiencies. Here, a diblock copolymer P3HT-bpoly(ethylene oxide) (PEO) is introduced to improve the interface between ZnO and P3HT. ZnO is synthesized via a block copol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
(78 reference statements)
0
4
0
Order By: Relevance
“…Neutrons are also uniquely sensitive to hydrogen and its isotope, deuterium. , With suitable instrumentation, GISANS has been increasingly used over the past three decades . Müler-Buschbaum pioneered the earliest studies on thin films by GISANS in an extensive series of studies on polymer thin films about surface roughness, interdiffusion of polymers, single-chain conformations, , dewetting of homopolymers and copolymers, hydration of micelles, adhesive-adherent interfaces, and composite materials for photovoltaic, magnetic, , and Li-ion battery applications. , Felcher and Adenwalla investigated Zeeman splitting when polarized neutrons impinged on a ferromagnetic surface at a grazing angle . GISANS has since been widely used to study micelles and other nanomaterials near surfaces and interfaces .…”
Section: Introductionmentioning
confidence: 99%
“…Neutrons are also uniquely sensitive to hydrogen and its isotope, deuterium. , With suitable instrumentation, GISANS has been increasingly used over the past three decades . Müler-Buschbaum pioneered the earliest studies on thin films by GISANS in an extensive series of studies on polymer thin films about surface roughness, interdiffusion of polymers, single-chain conformations, , dewetting of homopolymers and copolymers, hydration of micelles, adhesive-adherent interfaces, and composite materials for photovoltaic, magnetic, , and Li-ion battery applications. , Felcher and Adenwalla investigated Zeeman splitting when polarized neutrons impinged on a ferromagnetic surface at a grazing angle . GISANS has since been widely used to study micelles and other nanomaterials near surfaces and interfaces .…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25][26][27][28] The spray coating offers the advantages of easy up-scalability. 29 Combing the spin and spray method with a higher concentration of polyelectrolyte solutions is a feasible way to obtain homogeneous polymer films with tens of micrometers in thickness. Herein, a spin-spray-assisted (SSA-LbL) film assembly technique was developed to fabricate a thick polymer film with the merits of time and material-saving, compared with other LbL assembly methods.…”
Section: Introductionmentioning
confidence: 99%
“…The spin coating has been widely used to disperse the high viscosity materials on the planar substrate and create highly organized multilayers 17–28 . The spray coating offers the advantages of easy up‐scalability 29 . Combing the spin and spray method with a higher concentration of polyelectrolyte solutions is a feasible way to obtain homogeneous polymer films with tens of micrometers in thickness.…”
Section: Introductionmentioning
confidence: 99%
“…27 Spin-coated films have an increase in interface area and high heat transfer rate for heat removal process in large-scale fabrication. 24,28 The spin-coated graphene films exhibit highly ordered lamellar structure with high orientation of graphene which provides constant thermally conductive pathways. 29 From the previous literatures, it was found that various heat transfer techniques like TIM-based nanopaste materials and thin film coating techniques were used to analyze the performance of electronic components.…”
Section: Introductionmentioning
confidence: 99%